Pozzolanic reaction, basic properties, carbon reduction and visualisation of kerbstone prepared from recycled concrete - Chao-qiang Wang; Yan Ying; Sheng-hui Gao; Jian-shan Huang; Meng-sheng Shao (Case Studies in Construction Materials)
This study explores the key technologies for the preparation of fully recycled concrete kerbstone (RCK) and its frost resistance. It explores the physicochemical properties of recycled micropowder (RMP) and recycled aggregate (RA), and reveals the secondary hydration mechanism of RMP, thus providing new theoretical support for the global utilization of waste concrete resources. The optimal mix ratio for RCK were determined based on the changes in material properties and freezing resistance with varying dosages of RMP and RA. This study fills the current technological gap in the field of fully RCK internationally, and based on the principle of interfacial effects, the study reveals the interfacial morphological characteristics of RCK. The research results show that the physicochemical properties of RA meet the requirements of the Chinese standards ''Recycled coarse aggregates for concrete'' (GB/T25177–2010) and ''Recycled fine aggregate for concrete and mortar'' (GB/T25176–2010), while the pozzolanic activity of recycled micro-powder reaches 65.2 %, exhibiting significant secondary hydration reactivity. The optimized fully RCK demonstrate excellent compressive strength and frost resistance, meeting the relevant requirements of the ''Concrete kerbs'' (JC/T899–2016) and ''Standard for test methods of long-term performance and durability of ordinary concrete'' (BT 50082–2009). There are three kinds of interfacial transition zones in RCK. These zones reduce interface connectivity and weaken RCK's resistance to external moisture, chemicals, and other erosive factors. Moreover, the research through carbon emission analysis indicates that this technology can reduce carbon emissions by approximately 99 %, offering considerable environmental benefits. By combining Citespace visualization analysis, this study proposes a key technological system for the preparation of fully RCK. This study contributes to the international development of waste concrete resource utilization and offers a new pathway with ecological, environmental, and socio-economic implications.